PENGARUH ASPAL BUTON TERHADAP PROPERTIS TANAH EKSPANSIF - Selvia Agustina; Gatot Rusbintardjo; Lisa Fitriyana (Jurnal Infrastruktur, 2021)
The strength of pavement is highly depend on the quality of the subgrade. Pavement placed on poor subgrade will require sufficient thickness to be able to withstand traffic load. If the soil where the pavement will be constructed have low strength, then some efforts must be done to increase its strength. There are three methods to increase the soil strength, first by replacing the original soil with other better soil, the second method is by thickening the layers of pavement, and the third method is by strengthening the existing soil. In this research, the third method was used. Expansive clay soil was stabilized using Button Natural Rock Asphalt (BNRA). 20% to 35% of BNRA is finely ground to pass sieve #200. The Proctor, California Bearing Ratio (CBR), direct shear, and Atterberg Limit tests are conducted. The CBR test results indicate that the CBR value increases with increasing of BNRA content. CBR values resulted from the test are 2.89%, 3.13%, 3.36%, 3.91% for BNRA content 20%, 25%, 30%, and 35% respectively, or increase 166% from the CBR value of original soil. Meanwhile, direct shear test results cohesion ‘c’ also increase. These test results indicate that BNRA can increase the strength of expansive clay, and meet the requirements to be used for subgrade pavement.